PREFERENCES TOWARDS ORGANIC AND FUNCTIONAL YOGHURT IN REPUBLIC OF SRPSKA - Grubor, Aleksandar B.; Đokić, Nenad S.; Pavlović, Nataša Đ. (Economics of Agriculture, 2015)
This article presents the results of the research of preferences towards organic and functional yoghurt, conducted in Republic of Srpska, from January to May, 2014 (n=200). Generally, respondents do not consider whether yoghurt being or not being organic or functional as very important. They partially prefer functional yoghurts, but prefer yoghurts made from conventionally produced milk. For both, organic and functional food, consumers were divided into two segments – the frst which considered yoghurt being organic (or functional) among three the most important attributes of a product and the second segments comprising of all other respondents. Hereby, 8% of respondents belonged to the frst segment for organic and 20% for functional yoghurt. Compared to second segments, consumers belonging to the frst segment for organic yoghurt statistically signifcantly differ from others by valuating food importance for health more, while for functional yoghurt by assessing own physical health worse.